PENGARUH PERILAKU KARYAWAN TERHADAP PENERAPAN NORMA KESELAMATAN DAN KESEHATAN KERJA (K3) DI AREA PENAMBANGAN BATUBARA BAWAH TANAH PT. NUSA ALAM LESTARI SAWAHLUNTO, SUMATERA BARAT - Khurry Mu'amalla; Rijal Abdullah; Tamrin Kasim (Departemen Teknik Pertambangan FT UNP, 2014)
Wor k accident which often happen at PT. Nusa Alam Lestari are caused by unsafe action and unsafe condition.The main cause of the accidents is the insecure employees' behavior. Those work accidents may ha ve correlation on the implementation of The Safety and Occupational Health Norms. The purpose of this study is to determine the influence of employees' knowledge, attitude and action against the implementation of The Safety and Occupational Health Norms in Underground Coal Mining of PT. Nusa Alam Lestari. The type of this r esearch is correlation research whose goal is to find out whether there is the correlation between the two variables. The population of this research is the whole temporary and permanent employees remain at PT. Nusa Alam Lestari. The total of the employees is 156 people. The size of sample in this study was determinate by using the Slovin's formula which is obtained 61 people.Data collection was obtained by using questionnaire that has been tested for validity and reliability. Furthermore the data was processed by using the SPSS computer program. On multiple linear regression analysis is obtained regression equation: Y = 0,494 + 0,350X1 + 0, 389X2 + 0, 333X3 with significant value 0.000 < 0.05. In conclusion, there is the correlation between va riables of employees' knowledge, attitude, and action and the implementation of The Safety and Occupational Health Norms which collectively contribute significantly to the implementation of The Safety and Occupational Health Norms amounted to 56,4%.